An evaluation of resistance to change of the East London industrial development zone (ELIDZ) structural realignment - Moonieya, Vernon Craig (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
From Integrative Summary: This research paper comprises of three sections that include: an evaluation report, a literature review and the research methodology. The first section assesses the management of resistance to change as encountered during the ELIDZ structural re-alignment initiative. The assessment was done after the change initiative had been implemented to see what could be learnt from the exercise, in order to be better prepared for future change programmes. The implemented change was initiated by the CEO of the ELIDZ but its criticality in terms of purpose, or the need for the change was unclear to many employees at the time of initiation. An examination of the literature on change management highlighted the importance of managing resistance to change as part of a change initiative, so as to ensure a successful transition. The review of the literature on management of resistance to change in section 2 of this paper examines the definition of management of resistance to change and in particular, covers key factors like change readiness, participation in change and change communication. These key concepts underpin effective management of resistance during change. The literature on management of resistance to change with respect to the role of change readiness, participation in change and change communication was used to develop a questionnaire that was used to assess the ELIDZ change initiative. The questionnaire was developed in a Likert Scale format with questions across the spectrum of change readiness, change participation and change communication. Section 3 of this paper describes how the quantitative research was provided to the population sample of employees from the ELIDZ where the questions on change readiness, change participation and change communication was used to assess the effectiveness of management of resistance to change during the ELIDZ change initiative. In addition section 3 provides an explanation of how the results of the research were derived. The results on change readiness suggest that the ELIDZ change initiative did not address change readiness adequately. There is therefore a risk of resistance to change that could manifest. This also indicates that change readiness must be planned more thoroughly in future change endeavours. Most of the population sampled did not feel that they participated in the change initiative, suggesting that the ELIDZ did not address participation in the change initiative adequately. Not enabling employees to actively participate in the change is tantamount to decreasing the potential for acceptance of change and increasing the risk of resistance to change. In order to ensure that future change initiatives are not met with employee resistance to change, the ELIDZ should plan for employee participation throughout the change process. The extent to which change communication was addressed in the ELIDZ change initiative was demonstrated by very poor results. The results from the population sampled suggest that the change was not well communicated to employees. As change communication is known to reduce the potential for resistance to change, it is imperative for the ELIDZ to plan for comprehensive communication strategies to cover the change process for future change action.
Keywords: Organizational change -- South Africa -- East London -- Case studies; Organizational behavior -- South Africa -- East London -- Case studies; Industrial development projects -- South Africa -- East London -- Case studies; Organizational change -- Management -- South Africa -- East London -- Case studies; Management -- Employee participation -- South Africa -- East London -- Case studies; Communication in management -- South Africa -- East London -- Case studies; Industrial management -- South Africa -- East London -- Case studies